Neopterin and Soluble CD14 Levels as Indicators of Immune Activation in Cases with Indeterminate Pattern and True Positive HIV-1 Infection - (:unkn) unknown (PUBLIC LIBRARY SCIENCE, 2016)
Background We aimed to evaluate the roles of the plasma immune activation biomarkers neopterin and soluble CD14 (sCD14) in the indirect assessment of the immune activation status of patients with the indeterminate HIV-1 (IHIV-1) pattern and a true HIV-1-positive infection (PCG). Methods This cross-sectional and descriptive study included eighty-eight patients with the IHIV-1 pattern, 100 patients in the PCG, and 100 people in a healthy control group (HCG). Neopterin and sCD14 levels were determined by competitive and sandwich ELISA methods, respectively. Results Mean neopterin and sCD14 levels among those with the IHIV-1 pattern were significantly lower than among the PCG (p < 0.001 and p = 0.001, respectively), but they were similiar to those in the HCG (p = 0.57 and p = 0.66, respectively. Mean neopterin and sCD14 levels among the PCG were found to be significantly higher than among those with the IHIV-1 pattern (p < 0.001 and p = 0.001, respectively) and among those in the HCG (p = 0.001, p < 0.001, respectively). Neopterin did not have adequate predictive value for identifying those in the PCG (area under the curve [AUC] = 0.534; 95% CI, 0.463-0.605; p = 0.4256); sCD14 also had poor predictive value but high specificity (100%) for identifying those in the PCG (AUC = 0.627; 95% CI, 0.556-0.694; p = 0.0036). Conclusions While low levels of these two biomarkers were detected among those with the IHIV-1 pattern, they were found in high levels among those in the PCG. These two markers obviously cannot be used as a sceening test because they have low sensitivies. Taken together, we suggest that neopterin and sCD14 may be helpful because they both have high specificity (92%-100%) as indirect non-specific markers for predicting the immune activation status of individuals, whether or not they have true positive HIV-1.
Keywords: HUMAN-IMMUNODEFICIENCY-VIRUS; PREDICTS DISEASE PROGRESSION; ANTIRETROVIRAL THERAPY HAART; HIV-1/HIV-2 RAPID TEST; INTERFERON-GAMMA; SERUM NEOPTERIN; MICROBIAL TRANSLOCATION; PROGNOSTIC-SIGNIFICANCE; VIRAL LOAD; MARKERS